2013
DOI: 10.1002/jat.2901
|View full text |Cite
|
Sign up to set email alerts
|

Role of methotrexate exposure in apoptosis and proliferation during early neurulation

Abstract: Apoptosis and proliferation play important roles in embryonic development and are required for neural tube closure. The antifolate drug methotrexate (MTX) induces folate dysmetabolism by inhibition of dihydrofolate reductase and causes abnormal apoptosis and proliferation. In this study, we established an animal model of neural tube defects (NTDs) using MTX to investigate the role of apoptosis and proliferation in NTDs caused by folate deficiency. Differential gene expressions were studied by microarray and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…We observed these apoptotic features when DHFR function was blocked in Xenopus embryos. This is consistent with reports in other vertebrates where defects in folate metabolism also resulted in increased apoptosis during development (Lee et al, 2012; Sun et al, 2014; Tang et al, 2005; Wang et al, 2014). Moreover, we demonstrated that DHFR inhibition induced apoptosis is in part due to increased DNA damage.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We observed these apoptotic features when DHFR function was blocked in Xenopus embryos. This is consistent with reports in other vertebrates where defects in folate metabolism also resulted in increased apoptosis during development (Lee et al, 2012; Sun et al, 2014; Tang et al, 2005; Wang et al, 2014). Moreover, we demonstrated that DHFR inhibition induced apoptosis is in part due to increased DNA damage.…”
Section: Discussionsupporting
confidence: 93%
“…We show that DHFR deficiency specifically during early head and facial development causes a narrower midface and malformed mouth shape, due to loss of jaw muscle and cartilage elements. This is consistent with reported effects in mammals where folate deficiencies or mutations to major pathway components can also result in craniofacial defects and smaller head size (Burgoon et al, 2002; Momb et al, 2013; Tang et al, 2005; Wang et al, 2014; Zhao et al, 2013). Further, DHFR mutations are associated with cleft lip in humans (Martinelli et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Reports have shown that the occurrence of NTDs is associated with imbalance between cell proliferation and apoptosis. Studies have proved that disordered proliferation and apoptosis in animal models of NTDs were induced by hyperthermia [12], hyperglycemia [13], cyclophosphamide [14], or methotrexate (MTX) [15]. Therefore, cell proliferation and apoptosis have to be kept in dynamic balance during the formation of neural tube.…”
Section: Introductionmentioning
confidence: 99%